Analysis of student behavior in virtual learning environment depending on student assessments - Benko, Ľubomír; Reichel, Jaroslav; Munk, Michel (IEEE (Institute of Electrical and Electronics Engineers), 2015)
Virtual learning environment can nowadays provide good foundation for students to successfully manage any subject that is educated with the help of virtual learning environment. Backward analysis of student behavior in electronic course depending on their final marks, may reveal weaknesses of the course, or possible problem areas of teaching. This research is focused on analyzing the influence of behavior of students in electronic course on their final marks at the end of term. The authors present a detailed log file preprocessing procedure that makes it possible to examine the behavior of students in a virtual learning environment during the term. Individual electronic course activities were divided into interrelated logical groups and based on that were identified association rules between the content - course activities - course modules and the final marks. The rules represent the access of a particular group of students, who were divided according their final marks, to the created activity groups. The results of the analysis showed that the final marks correspond to the behavior of students in virtual learning environment. Despite that the research did not confirm the high degree of dependency, the results could help improve the teaching using the electronic course. The results also showed that repeating autotest tasks to improve the knowledge necessary for the final examination, did not bring the expected effect.
Analýza chování ve virtuálním vzdělávacím prostředí podle hodnocení studentů
Keywords: Computer aided instruction; Curricula; Education; Students; Teaching Backward analysis; Course modules; Počítačová výuka; Učební osnovy; Vzdělávání; Studenti; Didaktická analýza učiva; Programové sekce